دور القطاع الوقفي في تمويل الإنفاق الصحي - محمد، قريش; كوديد، سفيان Koudid, Sufian (المركز الجامعي عبدالحفيظ بوالصوف ميلة - معهد العلوم الاقتصادية والتجارية وعلوم التسيير, 2019)
This research aims to highlight the role of the waqf sector in the financing of health spending, so we will look to concepts related to waqf and health spending for a sample of countries, including Algeria, in order to show the differences in spending, as well as the role of the charitable sector in this, and we look to the role of waqf in the development of health spending in Algeria in the light of a range of international experiences, the experience of Kuwait , the UAE and the experience of Bill Gates.
يهدف هذا البحث إلى تسليط الضوء على دور القطاع الوقفي في تمويل الإنفاق الصحي، بحيث سنتطرق إلى المفاهيم المتعلقة بالوقف، ومن تم الإنفاق الصحي لعينة من الدول بما في الجزائر، وذلك بغية إظهار الفوارق في الإنفاق، وكذا دور القطاع الخيري في ذلك، ولنستشرف دور الأوقاف في تنمية الإنفاق الصحي في الجزائر على ضوء مجموعة من التجارب العالمية كالتجربة الكويتية والإماراتية وكذا تجربة وقف بيل غيتس.
Keywords: الرعاية الصحية -- الإنفاق الصحي -- الأوقاف الإسلامية -- الوقف الخيري -- الجزائر